Cervical Tuberculous Lymphadenitis in a Healthy Individual Following Latent Tuberculosis Treatment: A Case Report - Masahiro Yanagi (Respirology Case Reports)
ABSTRACT A 33‐year‐old healthy female, employed as a hospital‐based physical therapist, was exposed to a colleague diagnosed with pulmonary tuberculosis. Screening revealed a positive interferon‐gamma release assay (IGRA) result. She was diagnosed with latent tuberculosis infection (LTBI) and completed a 6‐month isoniazid (INH) regimen. Nine months post‐treatment, she presented to the otolaryngology department with right cervical swelling and ulceration. Polymerase chain reaction (PCR) of the pus confirmed Mycobacterium tuberculosis, establishing a diagnosis of cervical tuberculous lymphadenitis. She was referred to our hospital, where anti‐tuberculosis therapy led to symptom resolution. Post‐LTBI follow‐up primarily monitors for pulmonary tuberculosis, focusing on chest abnormalities or respiratory symptoms, particularly in high‐risk individuals with immunodeficiency. However, extrapulmonary tuberculosis can occur even in healthy individual's post‐LTBI treatment, necessitating vigilance.